EFFECT OF LIQUIDITY MANAGEMENT ON THE FINANCIAL PERFORMANCE OF LISTED CONSUMER GOODS COMPANIES IN NIGERIA - Adenike A OYEWUNMI (Malete Journal of Accounting and Finance, 2024)
Insolvency and bankruptcy have been the bane of many consumer goods companies CGCs due to frequent challenges such as slow inventory turnover, inefficient collection processes, and poor trade credit policies in consumer goods companies which have been negatively impacting cash flow, liquidity management, and customer payment behavior, thus resulting in bad debt and financial crisis. This research investigates the effects of liquidity management on the financial performance of listed consumer goods companies (CGCs) employing an expost-facto research design. All 21 listed consumer goods companies make up the population; fifteen of these were specifically selected using a judgmental sampling technique for reasons based on their capital bases, their readiness of data for ten years (2014–2023), and their listing on the NGX. Secondary data were used to analyze the financial accounts of the listed consumer goods companies. The panel OLS was the data analysis technique employed. The results revealed that liquidity management significantly affects ROA (p = 0.000000) and ROE (p = 0.000000) at a 1% significant level. The study concluded that liquidity management has a significant effect on consumer goods sectors in Nigeria. Therefore, it recommended that consumer goods companies invest in strategies that can increase profitability without significantly compromising liquidity.